Investigation on structural and optical properties of ZnO nanoparticles ingrained grafitic carbon nitrides. (2022) - Sangwan, Reetu; Yadav, Kavita; Barala, Monika; Mohan, Devendra
Abstract: The present study focus on nanoparticles of ZnO incorporated in grafitic carbon nitrides. Synthesis of ZnO nanoparticles grafted grafitic carbon nitride was successfully achieved by thermal decomposition of zinc acetate dihydrate and urea at 600˚C in muffle furnace . Urea is nitrogen rich precursor that act as a reducing agent as well as gets converted to grafitic carbon nitride .The crystal structure of the sample has been explored by X-ray diffraction spectra. The average crystallites size before and after the grafting are 31.89 nm, 20.86 nm, respectively. The optical properties of the grafted sample has been studied using UV–VIS. measurements. Scanning electron microscopy (SEM) shows the morphology of ZnO nanoparticles ingrained in graphitic carbon nitride with size ̴ 30 nm. Elemental composition by EDX image confirms the composite consisting of Zn, O, C and N elements.